Africaphes lineatus sp. nov., a new species of Stenichnini from Rwanda (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2026)
The recently described genus Africaphes Jałoszyński so far comprised two species, A. quadripunctatus Jałoszyński, and A. bipunctatus Jałoszyński, known to occur respectively in Burundi and Rwanda. A new species is described, based on a specimen collected in Rwanda, A. lineatus sp. nov. All three species of Africaphes are microscopic beetles, ranging from 0.95 to 1.15 mm, and unique in having a narrow median longitudinal slit on the head in males, presumably a glandular opening, which in each species is of a different length and placement, and only in A. quadripunctatus additionally accompanied by round pits and modified setae.